Answer: Horizontal asymptote is and vertical asymptotes are
Step-by-step explanation:
Since we have given that
We need to find the horizontal and vertical asymptotes.
Since vertical asymptotes will occur where the denominator becomes zero.
So, here denominator is
Now,
And the horizontal asympototes will occur when the coefficient of higher degree of numerator is divided by coefficient of higher degree of denominator.
Hence, horizontal asymptote is and vertical asymptotes are
Step-by-step explanation:
x²+ y² -12x - 18y +17 = 0 means : (x²-12x+36)-36+(y²-18y+81)-81-27 =0
(x-6)²+(y-9)² =12²....standard form when the center is (-6 , 9) and radius 12
Hey Jackson!
-4x + 3y = 3
y = 2x + 1
Ok so what we need to do is solving y= 2x + 1 for y.
So let's start by using the substitution method :)
Substitute 2x + 1 for y in -4x + 3y = 3
-4x+ 3y = 3
-4x + 3(2x + 1) = 3
-4x + (3)(2x) + (3)(1) = 3
-4x + 6x + 3 = 3
2x + 3 = 3
Subtract 3 on both sides
2x + 3 - 3 = 3 - 3
2x = 0
x = 0/2
x = 0
So now since we find the number for x, we gonna use it to help us find the value for y.
To find y, we need to substitute 0 for x in y = 2x + 1
y = 2x + 1
y = 2(0) + 1
y = 0 + 1
y = 1
Thus,
The answer is: y = 1 and x = 0
How to graph?
You need to go on the thing where they put the numbers. y is located on top which has the positive numbers. So when you get there, make a line that comes from the top right side all the way to the bottom left sides. Remember that y = 1 so the line must pass through 1
I am not good with explanation. So I'll leave the graph down below then you'll see what I am talking about :)
Let me know if you have any questions. As always, it is my pleasure to help students like you!
Answer:
2.1 gaallons of honey
Step-by-step explanation:
If you have to istrubute things then its obvous you need to divide something. To get 19 equally into 9 containers you divide 19 by 9 an get 2.1
I hope this helped